PENERAPAN METODE ADZ-DZIKR DALAM MENINGKATKAN BELAJAR MEMBACA AL-QUR’AN DI TPQ MIFTACHUL ROHMAH AL-HIDAYAH KUTOREJO MOJOKERTO - Ilmi, Khafidotul (ILJ: Islamic Learning Journal, 2023)
S Studying the Qur'an is an obligation ordered by Allah SWT. to every Muslim and Muslimah, Apart from being a necessity, the Qur'an is a book of guidance which shows the way to happiness in the world and the hereafter, Given the importance of studying (studying the Qur'an) Rasulullah SAW. Suggest learning the Qur'an as early as possible because at that time it contained a very large and strong potential. This study uses a qualitative approach, which has a natural setting approach as a source of direct, descriptive data, besides that the process is more important than the results. Globally qualitative is used in observing social life, history, social activities and religious behavior. Application of Learning to Read the Qur'an with the Adz-dhikr method at TPQ Miftahul Rohmah Al-Hidayah Learning is interpreted as a result of interaction between stimuli and responses, the process of changing behavior as a learning process should be adapted to the stage of child development. This is reinforced by Piaget's opinion that children's cognitive development must go through a learning process, and be adjusted to the stages.